2018
DOI: 10.1103/physreva.98.013813
|View full text |Cite
|
Sign up to set email alerts
|

Tunable bandwidth and nonlinearities in an atom-photon interface with subradiant states

Abstract: Optical non-linearities at the single photon level are key features to build efficient photon-photon gates and to implement quantum networks. Such optical non-linearities can be obtained using an ideal two-level system such as a single atom coupled to an optical cavity. While efficient, such atom-photon interface however presents a fixed bandwidth, determined by the spontaneous emission time and thus the spectral width of the cavity-enhanced two-level transition, preventing an efficient transmission to bandwid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
(113 reference statements)
1
8
0
Order By: Relevance
“…We hereafter introduce an effective one dimensional atom where the system bandwidth and mode coupling are largely independent. We consider the system consisting of two atoms represented by two level systems (TLS) strongly coupled through a dipole-dipole interaction and coupled to the same cavity mode [22]. The TLS have ground states |g i and excited states |e i (i = 1, 2), with transition energies E |ei − E |gi = ω i and a dipole-dipole coupling strength Ω 12 [19].…”
Section: A Tunable One Dimensional Atommentioning
confidence: 99%
See 2 more Smart Citations
“…We hereafter introduce an effective one dimensional atom where the system bandwidth and mode coupling are largely independent. We consider the system consisting of two atoms represented by two level systems (TLS) strongly coupled through a dipole-dipole interaction and coupled to the same cavity mode [22]. The TLS have ground states |g i and excited states |e i (i = 1, 2), with transition energies E |ei − E |gi = ω i and a dipole-dipole coupling strength Ω 12 [19].…”
Section: A Tunable One Dimensional Atommentioning
confidence: 99%
“…1, ∆ 12 acts as an effective coupling between the states |+ and |− . The system eigenstates |− eff and |+ eff are then a superposition of both symmetric and antisymmetric states for which simple analytical expressions can be obtained when γ Ω 12 , g [22]:…”
Section: A Tunable One Dimensional Atommentioning
confidence: 99%
See 1 more Smart Citation
“…They allow to confine and tune the electromagnetic field at subwavelength scales. The plasmonic mode can play a crucial role, mediating and adjusting the coupling in the near field [15][16][17]. This approach can also be extended to obtain phase locking between 2D arrays of spasers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, theoretical studies [34][35][36][37][38] have shown that the enhancement and tunability of single photon emission are possible through interfaces based on two-emitter systems coupled to a cavity mode. In their scheme, tunable bandwidth and Purcell enhancement are achieved by dynamical control of the collective states of the two emitters coupled by dipolar interaction.…”
Section: Introductionmentioning
confidence: 99%